Kesalahan Siswa Kelas VIII SMP Negeri 13 Mataram dalam Menyelesaikan Soal Cerita Materi Sistem Persamaan Linear Dua Variabel Tahun Pelajaran 2019/2020 - Rangga Faradisha; Sripatmi Sripatmi; Eka Kurniawan; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2021)
The Errors made by students in completed math problems can be indicators of the low learning achievements. Based on these problems, this study aim to know the categories of errors and the relation or correlations of the types of errors each Polya's steps in solving the material story of system two linear equations students all grade VIII of SMP Negeri 13 Mataram academic year 2019/2020. The population in this study was all student grade VIII of SMP Negeri 13 Mataram. Samples used the Proportionate Stratified Random Sampling technique. Data collection used test essai and interview which had beenvalidated. Error categories were analyzed used interval categories of error levels and for the relation or correlations between types of errors used the Pearson product moment correlation. The results showed that students mistakes for high abilities in the low category, for the medium abilities in the high category and for the low ability level in the high category. Based on data analysis it was found three categories relationships types of errors : namely, sufficient, strong and very strong categories. The level of relationship strong enough for this type of error to understand the problem and formulate a plan, misunderstanding the problem and carrying out the plan, misunderstanding the problem and re-checking. Level of strong links to types of mistakes Arranging plans and executing plans, mistakes compiling plans and re-checking. The level relationship very strong for type error implementing the plan by checking again. When completed a problem should be solved systematically in stages to avoid mistakes that will be made at a later stage.